2015
DOI: 10.1179/1743286315y.0000000022
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic fracturing operations in mining: conceptual approach and DFN modeling example

Abstract: Most of the hydraulic fracturing experiments by the mining industry in hard rocks were conducted to precondition the rockmass with the aim of improving caveability and fragmentation for block caving mining operations through the creation of hydraulic fractures (HF). Based on an extensive literature survey and models, it is suggested that successful preconditioning could be obtained through hydraulic treatment of the rockmass. This paper discusses the interaction between hydraulic fluid injection and the pre-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Similarly, laboratory investigations by Doe and Boyce (1989) showed that the stress orientation defines hydraulic fracture propagation only for a stress field anisotropy ratio σ 1 /σ 3 > 1.5. At near isotropic stress conditions the fractures branch more strongly and without a preferred propagation direction, a phenomenom often referred to as high fracture complexity (e.g., Katsaga et al, 2015). During large-scale stimulations, there is a tendency for seismic clouds to develop perpendicular to the minimum principal stress direction σ 3 (Häring et al, 2008;Evans et al, 2005), particularly for HF operations (e.g., Rutledge et al, 2004), although for HS stimulations in crystalline rocks there are many examples in which the seismicity cloud is oblique to the σ 3 direction (e.g., Block et al, 2015;Murphy and Fehler, 1986;Pine and Batchelor, 1984), presumably reflecting the complex interplay between stress and the pre-existing fracture population that is suitably oriented for slip reactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, laboratory investigations by Doe and Boyce (1989) showed that the stress orientation defines hydraulic fracture propagation only for a stress field anisotropy ratio σ 1 /σ 3 > 1.5. At near isotropic stress conditions the fractures branch more strongly and without a preferred propagation direction, a phenomenom often referred to as high fracture complexity (e.g., Katsaga et al, 2015). During large-scale stimulations, there is a tendency for seismic clouds to develop perpendicular to the minimum principal stress direction σ 3 (Häring et al, 2008;Evans et al, 2005), particularly for HF operations (e.g., Rutledge et al, 2004), although for HS stimulations in crystalline rocks there are many examples in which the seismicity cloud is oblique to the σ 3 direction (e.g., Block et al, 2015;Murphy and Fehler, 1986;Pine and Batchelor, 1984), presumably reflecting the complex interplay between stress and the pre-existing fracture population that is suitably oriented for slip reactivation.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with a sufficiently high-viscosity fluid prevents the fluid from leaking into the surrounding rock, which results in a significant stress concentration. As the injection rate increases, the leakage into the surrounding rock becomes less important [43]. Moreover, poroelastic stress changes can locally modify the given tectonic stress regime [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…When carrying out geophysical study, a set of seismic equipment (Figure 1) was used to record data, consisting of: autonomous seismic recorders "R-1", providing seismic data in digital format (1) and geophones (2), determining the number of channels in the performed research. A percussive source of mechanical vibrations is used to generate the signal.…”
Section: Methodologiesmentioning
confidence: 99%
“…The use of hydraulic fracturing in coal mines can meet different requirements. Hydraulic action is distinguished in order to ensure the intensification of methane recovery from coal seams, and to eliminate the negative effect of a difficult-to-collapse roof [1][2][3][4]. For each of the listed objectives fracturing processes are characteristic and, as a consequence, changes in the geomechanical composition of rocks in the area of hydraulic impact are observed.…”
Section: Introductionmentioning
confidence: 99%